Assessing Environmental, Safety, Regulatory, and Dispute Resolution Challenges in Hydrogen Pipeline Infrastructure - Timalsina, Saksham; Zhang, Chengyi; Hada, Srishti; Demirkesen, Sevilay (Asce-Amer Soc Civil Engineers, 2025)
Hydrogen pipelines offer efficient large-scale fuel transport for clean energy but face unique challenges. With issues like embrittlement, strict safety requirements, and complex environmental and Indigenous concerns, there are distinctive legal and policy hurdles for this emerging infrastructure, different from traditional natural gas or oil pipelines. This study navigates the legal and regulatory challenges in hydrogen pipeline construction through environmental and Indigenous perspectives based on the multiple-case synthesis of the crude oil pipeline construction projects. The lessons from this comparative analysis of oil pipeline projects provide valuable insights into anticipating and mitigating potential conflicts in future hydrogen pipeline developments. The findings are further supported by a semistructured expert panel review with six experts, with artificial intelligence (AI) used as a supplementary tool to assess their knowledge of these aspects. These insights have guided the formulation of hydrogen-specific regulations that address the unique challenges, emphasizing Indigenous perspectives in environmental impact assessments (EIAs) and the development of policies aimed at reducing disputes and limiting political interference. This will help in the project's timely, under-budget completion and enhanced outcome. Further, the improved stakeholder relationships and increased project benefits will attract more investors, contributing to clean energy and zero-carbon-emissions policies.
Keywords: Hydrogen pipelines; Safety; Disputes; Environmental impact assessment (EIA); Indigenous involvement; Generative pretrained transformer (GPT)